2008
DOI: 10.1007/s12011-008-8297-2
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Copper and Iron in Biological Samples of Viral Hepatitis (A–E) Female Patients

Abstract: There is accumulative evidence that the metabolism of iron and copper is altered in viral hepatic diseases, and these nutrients might have specific roles in their pathogenesis and progress. The aim of present study was to compare the level of copper (Cu) and iron (Fe) in biological samples (serum, urine, and scalp hair) of female patients suffering from different viral hepatitis (A, B, C, D, and E; n = 253) of age range 31-45 years. For comparative study, 95 healthy females of the same age group residing in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…This technique has a need for solubilization of the analyte and complete or partial decomposition of the matrix using convective systems, microwave ovens, or dry ashing [24,25]. The main advantage of microwave-assisted samples pretreatment is its requirement of a small amount of mineral acids and a reduction in the production of nitrous vapors [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…This technique has a need for solubilization of the analyte and complete or partial decomposition of the matrix using convective systems, microwave ovens, or dry ashing [24,25]. The main advantage of microwave-assisted samples pretreatment is its requirement of a small amount of mineral acids and a reduction in the production of nitrous vapors [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…To discriminate between these scenarios, we measured content of several metals in the urine (Figure 4). Specific excretion was expected to produce a selective increase in copper concentration, whereas a mechanism in which hepatic cell death is the primary pathway would likely change levels of several metals [12], [13]. ICP-MS analysis confirmed that Cu levels were high in Atp7b −/− urine, compared with wild-type and increased with age (Figure 4A).…”
Section: Resultsmentioning
confidence: 95%
“…Previous reports have stated that the host response to HCV infection may be primarily dependent on the human leukocyte antigen system. However, other factors, such as copper, may also influence the host response because changes in copper levels in patients with HCV infection have been reported [15,36,37] . We propose that the H1069Q mutation of the ATP7B gene may be an important modifier in patients with HCV infection.…”
Section: Discussionmentioning
confidence: 99%